2019
DOI: 10.1159/000504315
|View full text |Cite
|
Sign up to set email alerts
|

Educational Program in Complementary and Alternative Medicine for Cancer Self-Help Groups

Abstract: Background: The use of complementary and alternative medicine (CAM) among cancer patients is estimated to be approximately 40%. In self-help groups there is a need for information about CAM. This pilot study aimed to develop and evaluate a CAM educational program for cancer selfhelp groups. Methods: The educational program was developed in cooperation with health professionals and representatives of cancer self-help organizations. Participants were trained to increase their knowledge about CAM, to reflect thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…This study was part of the collaborative research project Competence Network of Complementary Medicine in Oncology (KOKON), which focused on CAM information and supportive programs for improving consulting skills for health care professionals and information about CAM in cancer patients [35,36]. In our study, we educated cancer SHG leaders about CAM in oncology based on a concept which we developed in a previous study [37]. As a result, we created a structured manual for the group leaders (GL) to facilitate them to educate the group participants (PT) in CAM.…”
Section: Methodsmentioning
confidence: 99%
“…This study was part of the collaborative research project Competence Network of Complementary Medicine in Oncology (KOKON), which focused on CAM information and supportive programs for improving consulting skills for health care professionals and information about CAM in cancer patients [35,36]. In our study, we educated cancer SHG leaders about CAM in oncology based on a concept which we developed in a previous study [37]. As a result, we created a structured manual for the group leaders (GL) to facilitate them to educate the group participants (PT) in CAM.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, the role of cancer health literacy is inconclusive. While some studies showed that the patients with higher CAM use have signi cantly lower health literacy scores (Conrady & Bonney, 2017; Wilhelm & Euteneuer, 2021), others showed that they also can have more positive attitudes toward CAM because they tend to rely on rapidly available and unscienti c, easily found sources of information (Dişsiz & Yilmaz, 2016;Jablotschkin et al, 2020). Therefore, we will also examine the role of cancer health literacy for both groups of women and its association with CAM use and attitudes.…”
Section: Psychological Predictors Of Cam Usementioning
confidence: 99%